Visiting the Remains of the Pakuan Pajajaran Palace: Exploring Cultural Values in the Batu Tulis Area of Bogor - Syarifuddin Latif, Bagus; Ari Wibowo, Toni; Pradini, Gagih; Aditya Pratama, Reza (Ann Publisher, 2024)
The Batu Tulis area in Bogor is a historical site that contains traces of the Pakuan Pajajaran Palace, a large kingdom that once existed among the Sunda Tatars. This research aims to uncover the cultural values ​​that still remain in the area through